Incorporating a palaeo-perspective into Andean montane forest restoration - Loughlin, Nicholas J. D.; Gosling, William D.; Duivenvoorden, Joost F.; Cuesta, Francisco; Mothes, Patricia; Montoya, Encarni (Frontiers in Conservation Science, 2022)
Reference ecosystems used in tropical forest restoration lack the temporal dimension required to characterise a mature or intact vegetation community. Here we provide a practical ‘palaeo-reference ecosystem’ for the eastern Andean forests of Ecuador to complement the standard ‘reference ecosystem’ approach. Pollen assemblages from sedimentary archives recovered from Ecuadorian montane forests are binned into distinct time periods and characterised as 1) Ancient (pre-human arrival), 2) Pre-European (Indigenous cultivation), 3) Successional (European arrival / Indigenous depopulation), 4) Mature (diminished human population), 5) Deforested (re-colonisation), and 6) Modern (industrial agriculture). A multivariate statistical approach is then used to identify the most recent period in which vegetation can be characterised as mature. Detrended correspondence analysis indicates that the pollen spectra from CE 1718-1819 (time bin 4 – Mature (diminished human population)) is most similar to that of a pre-human arrival mature or intact state. The pollen spectra of this period are characterised by Melastomataceae, Fabaceae, Solanaceae and Weinmannia. The vegetation of the 1700s, therefore, provides the most recent phase of substantial mature vegetation that has undergone over a century of recovery, representing a practical palaeo-reference ecosystem. We propose incorporating palynological analyses of short cores spanning the last 500 years with botanical inventory data to achieve more realistic and long-term restoration goals.